Cassia leptophylla, Gold Medallion Tree - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS, 2012)
The gold medallion tree is planted primarily as a shade tree or as a decorative specimen for the yard or street. Many people like this tree because of its fast growth rate and showy, bright yellow clusters of flowers that bloom in the summer months. This tree loses its leaves for a very short period each year, but leaves are quickly replaced. Pruning the tree to one main leading stem from which major branches are attached can help increase its strength and sturdiness against strong wind events. The golden medallion tree is also naturally pest resistant, and as long as it is grown in areas where the temperature does not drop below freezing, it is an easy tree to care for. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.